Safety and effectiveness of intrastromal corneal ring segment implantation at Al-Dharan Eye Specialist Hospital, Al-Dharan, Saudi Arabia - Alaqsam, Abdulaziz; AL-Jindan, Mohanna; Almahmod, Ammar; Gosadi, Ibrahim (International Surgery Journal, 2019)
Background: Intrastromal corneal ring segment (ICRS) implantation is one of the treatment options of keratoconus. This study is aiming to evaluate safety and effectivness of ICRS implantation at Al-Dharan Eye Specialist Hospital. Methods: This study is a descriptive retrospective case series study. The target population of this study is patients diagnosed with corneal ectasia who underwent ICRS implantation in Al-Dharan Eye Specialist Hospital, Al-Dharan, Saudi Arabia. Preoperative and postoperative data about uncorrected visual acuity (UCVA), best spectacle–corrected visual acuity (BSCVA), manifest refraction, keratometry, applanation tonometry, corneal topography, and slit-lamp biomicroscopy and indirect ophthalmoscopy were retrieved from medical records of department of Medical Archive. Paired students t-test was used to compare preoperative and postoperative means of study variables. Results: The total number of recruited patients in this study was 57 patients where 62% of them were males. Sixty-six treated eyes were included in this study where no intra-operative complications were recorded. Upon comparing the mean preoperative data to the mean postoperative data at three months, six months and one year intervals, an overall improvement in the measured outcomes was witnessed. UCVA, BSCVA, and keratometric readings exhibited a statistically significant improvement when comparing preoperative with one-year postoperative findings (p<0.001). Conclusions: The findings of this study indicate that ICRS implantation is a safe and effective treatment for keratoconus.